Religious Moderation of Millennial Generation at Islamic Higher Education in Eastern Indonesia - Zuhri, Barsihannor; Tahir, Gustia; Arbianingsih, Arbianingsih; Aksa, Aksa (AL-TAHRIR, 2023)
This research examines the religious moderation of the millennial generation in Islamic Higher Education in Eastern Indonesia and identifies the most dominant factors contributing to religious moderation. Cross-Sectional Study (CSS) method measures religious moderation through four pillars at the same time: national commitment, religious tolerance, conflict avoidance (non-violence) and accommodation of local culture. The respondents of this research are   millennial generations studying at the Islamic Higher Education in Eastern Indonesia. This research used the Consecutive Sampling with a total sample of 592 people. The research results show that religious moderation among millennial students in Eastern Indonesia is categorized as low concerning national commitment, religious tolerance, avoiding conflict (non-violence), and accommodation of local culture. The most dominant factors influencing the religious moderation of the millennial generation are social media and religious extra-campus curriculum.